2018
DOI: 10.1038/s41598-018-26999-w
|View full text |Cite
|
Sign up to set email alerts
|

Lobohedleolide suppresses hepatitis C virus replication via JNK/c-Jun-C/EBP-mediated down-regulation of cyclooxygenase-2 expression

Abstract: Hepatitis C virus (HCV) chronically infects 2–3% people of the global population, which leads to liver cirrhosis and hepatocellular carcinoma. Drug resistance remains a serious problem that limits the effectiveness of US Food and Drug Administration (FDA)-approved direct-acting antiviral (DAA) drugs against HCV proteins. The objective of our study was to discover new antivirals from natural products to supplement current therapeutics. We demonstrated that lobohedleolide, isolated from the Formosan soft coral L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Thus, any defect in the mitochondrial transmembranous potentiality gives rise to a cascade of apoptosis-related signals. Moreover, Lin et al [39] declared that COX-2 is expressed in response to diverse inflammatory intracellular and extracellular stimuli such as chemicals, viral infections and ROS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, any defect in the mitochondrial transmembranous potentiality gives rise to a cascade of apoptosis-related signals. Moreover, Lin et al [39] declared that COX-2 is expressed in response to diverse inflammatory intracellular and extracellular stimuli such as chemicals, viral infections and ROS.…”
Section: Discussionmentioning
confidence: 99%
“…COX-2 expression is tightly controlled in most tissues [39] and is almost unnoticeable under normal physiologic conditions [7] . For this reason, the cells of SMGs and EGs in the control group of this study revealed a negative cytoplasmic and nuclear immunoreactivity to COX-2 with a moderate nuclear reaction in very few acini of SMGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cembranolides, possessing an α-methylene lactone ring, have been discovered as potent cytotoxic agents to a limited panel of cancer cell lines, for example, 14-deoxycrassin [ 20 ], and as significant anti-inflammatory agents, for example, sinulariolone acetate [ 21 ]. Additionally, cembranoids and related compounds from other coral species were also found to have notable antiviral [ 22 ], anti-inflammatory [ 23 , 24 ], and antiproliferative [ 25 , 26 , 27 , 28 ] activities. A wide variety of chemical diversity and biological activity of cembranoids encouraged us to search for more natural products from soft coral S .…”
Section: Introductionmentioning
confidence: 99%
“…Western blotting results showed that cembranoid 2 at 10 µM inhibited iNOS expression, which reduced the protein level to 28.50%, as compared with cells in the control group treated with LPS only (Table 2). In previous studies, cembranoid 2 was reported to exhibit extensive bioactivities such as cytotoxic [3,5], antiviral [4,16,17], and anti-inflammatory [16,[18][19][20] activities, and the anti-inflammatory activity of 2 has been evaluated and revealed that 2 is effective against both carrageenin induced edema and cotton pellet implantation rat models [18]. Lobocrassin I (1) did not show activity, implying that the exo-methylene substituent at C-15 enhanced the bioactivity in comparison with cembranoid 2.…”
mentioning
confidence: 99%